Analisis Penentuan Harga Kamar Hotel Dengan Fuzzy Logic Metode Sugeno Berdasarkan Kebutuhan Pelanggan Di Kota Batam - Anggia Dasa Putri; Tukino Tukino (LPPM Universitas Putera Batam, 2023)
Determining the right hotel room pricing is a critical aspect of hotel management. In Batam City, a popular destination for both tourism and business, adjusting hotel room prices based on customer needs has become increasingly important. This research focuses on the utilization of Fuzzy Logic Sugeno Method to analyze and determine hotel room prices that can be tailored to the preferences and requirements of customers in Batam City. The Sugeno Method is a powerful technique in fuzzy logic that allows for qualitative modeling of customer preferences. This research integrates historical hotel room data, weather data, city event data, and customer preferences collected through surveys and sentiment analysis. Subsequently, this method is employed to generate membership functions that link input variables, such as weather, to the output variable, which is hotel room price. The research findings demonstrate that this approach can yield hotel room prices that are more aligned with customer preferences based on factors such as weather and city events. This aids hotels in Batam City in optimizing their revenue by offering competitive and enticing prices to potential customers. This research makes a significant contribution to the development of smarter pricing strategies in the hotel industry, with a focus on customer satisfaction and revenue enhancement.